Factors related to the use of religious coping by informal caregivers: an integrative review - Farinha,Francely Tineli (2021)
ABSTRACT Objectives: to identify the factors related to the use of religious coping in informal caregivers. Methods: integrative literature review carried out through a search in the databases LILACS, PubMed, Scopus, Web of Science, and CINAHL, in addition to the Virtual Health Library and SciELO. The study selected primary articles in English, Portuguese, and Spanish, using the descriptors Coping Behavior, Caregivers, Spirituality, and Religion, which were combined with each other and with synonyms. There was no time limit for the publications. Results: nine articles were selected. Factors related to the use of religious coping in informal caregivers included: having an advanced age, experiencing traumatic situations, being under overload, being a spouse or mother, caring for hospitalized individuals, or for those with chronic diseases and high degrees of dependence. Conclusions: the factors related to the use of religious coping are multifaceted and involve physical, psychological, psychosocial, and situational aspects.